Software development hour with Sam Newman. (O'Reilly Media, Inc., 2023)
Join us for a special conversation with Sam Newman and Marianne Bellotti, best-selling author, builder of the data infrastructure for the United Nations, and fixer of some of the oldest and most complicated computer systems in the world as part of United States Digital Service. They'll discuss how to tame and modernize complex systems and explain why any kind of modernization or large-scale migration requires thinking about the people side of the problem in addition to the technical challenges to ensure success. This is a chance for you to from Sam and Marianne about software development, how to best manage migrations, and their own career journeys. They'll spend a few minutes covering the trends that are influencing software, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Learn what really matters for software design Discover best practices for modernizing complex systems Find out what's coming next for software development This recording of a live event is for you because... You want the chance to hear from Sam Newman and Marianne Bellotti about software development. You want to keep up with the latest developments in engineering practice. Recommended follow-up: Read Building Evolutionary Architectures, second edition (book) Listen to The Manager's Path (audiobook) or read the book Read The Staff Engineer's Path (book).